2019
DOI: 10.1038/s41566-019-0439-x
|View full text |Cite
|
Sign up to set email alerts
|

Computational time-of-flight diffuse optical tomography

Abstract: Imaging through a strongly diffusive medium remains an outstanding challenge in particular in association with applications in biological and medical imaging. Here we propose a method based on a single-photon time-of-flight camera that allows, in combination with computational processing of the spatial and full temporal photon distribution data, to image an object embedded inside a strongly diffusive medium over more than 80 transport mean free paths. The technique is contactless and requires one second acquis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 35 publications
0
76
0
Order By: Relevance
“…Indeed, in the last years several clinical and diagnostics applications [8,131] adopted DOT due to its capability to improve the imaging of deep inhomogeneities of the medium (e.g., tumor, local changes in O 2 Hb/HHb due to brain activation, etc.). The technological improvements in terms of both detectors (matrix of small detectors or large area ones) and detection electronics allows one to have faster measurements, thus going in the direction of real-time tracking of buried objects [132][133][134][135]. Additionally, the use of multiple-view acquisitions coupled to the tomographic reconstruction enables: (i) to overcome the limitation in spatial resolution typical of the diffuse optics; (ii) to improve the quantification of the absorption and scattering coefficient of the inclusion [136][137][138].…”
Section: Tomographymentioning
confidence: 99%
“…Indeed, in the last years several clinical and diagnostics applications [8,131] adopted DOT due to its capability to improve the imaging of deep inhomogeneities of the medium (e.g., tumor, local changes in O 2 Hb/HHb due to brain activation, etc.). The technological improvements in terms of both detectors (matrix of small detectors or large area ones) and detection electronics allows one to have faster measurements, thus going in the direction of real-time tracking of buried objects [132][133][134][135]. Additionally, the use of multiple-view acquisitions coupled to the tomographic reconstruction enables: (i) to overcome the limitation in spatial resolution typical of the diffuse optics; (ii) to improve the quantification of the absorption and scattering coefficient of the inclusion [136][137][138].…”
Section: Tomographymentioning
confidence: 99%
“…Experimental and theoretical work have demonstrated that under the condition of µ a µ s which is exactly the case of our application, light propagation in the medium falls into a strongly diffusive regime. Light within the medium essentially behaves like heat [19] and the photon transport can be modeled by a diffusion approximation with sufficient accuracy [15].…”
Section: Basic Principles Of Fmtmentioning
confidence: 99%
“…Solution therefore does not only involve calculation of optical properties but must also consider scattering effects inside medium. Thus, instead of apply commonly applicable direct method for solving such problems, inversion techniques are considered to evaluate which material properties would have created original signal [14]- [19].…”
Section: Numerical and Simulation Modellingmentioning
confidence: 99%
“…This trans-illuminated light is scattered through multiple tissues layers and structures present inside tissues. This trans-illuminated light then converted into a series of voltages to amplify, filtered and digitized to construct an image [11] [12] [13] [14]. The data are developed either through time varying intensities or steady state complex intensities of light that have measurable amplitude and phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation